Estudio comparativo entre bases de datos temporales y bases de datos relacionales aplicado a historias clínicas electrónicas (2015)
Choosing a database model when a system is developed is a decision that establishes the course of a project, and understanding the advantages and disadvantages of these models provides the starting point. This article reflects on the comparison between relational and temporary databases by evaluating their performance in a case study: the management of electronic medical records. The process starts by selecting desirable features and sub-features of the DBMS and the subsequent design of the case study and the choice of representative managers of each model. All of this having as purpose to provide a framework for future projects within the field of telemedicine, electronic medical records and mostly health systems involving temporary data storage.